Microstructural design of cellular 3 YTZ-Al2O3 ceramic membranes. Issue 1 (1st January 2021) - Ivanova, Yu A.; Lopes, D.V.; Durana, E.; Lisenkov, A.; Frade, J.R.; Kovalevsky, A.V.
Abstract: Porous 3 YTZ-Al2 O3 membranes were processed aiming controlled cellular microstructures for potential separation and electrochemical applications. The processing method relies on emulsification of mixed suspensions of Al2 O3 and 3 YTZ powders in sunflower oil. Taguchi experimental planning was used to seek guidelines for optimization of microstructural and structural characteristics, including porosity, phase composition and percolation of resulting membranes. Effects of alumina content, oil:suspension ratio, firing temperature and 2-step firing were evaluated by a correlation matrix and multivariate fitting. This analysis provided interpretation for prevailing effects on open and closed porosity, relative porosity loss during firing, and relevant microstructural and structural effects. The results demonstrate that the content of alumina plays key effects on partial transformation of tetragonal to monoclinic zirconia and on cell size. Percolation was analyzed by impedance spectroscopy, revealing that it is determined by series association of resistance to transport across the open cells and internal interfaces, ascribed to interruptions of open cell paths.